2002
DOI: 10.1110/ps.0202102
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic conformational fluctuations along the reaction coordinate of cytidine deaminase

Abstract: Analysis of the crystal structures for cytidine deaminase complexed with substrate analog 3-deazacytidine, transition-state analog zebularine 3,4-hydrate, and product uridine establishes significant changes in the magnitude of atomic-scale fluctuations along the (approximate) reaction coordinate of this enzyme. Differences in fluctuations between the substrate analog complex, transition-state analog complex, and product complex are monitored via changes in corresponding crystallographic temperature factors. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…occurring between amino acids in a real protein. In a previous publication, we showed that several physical descriptors can be used to predict the average crystallographic temperature factor of a given amino acid residue in the body of cytidine deaminase. This work quantified and modeled the long appreciated fact that amino acid residues enjoy different degrees of conformational freedom in different regions of the enzyme molecule .…”
Section: Enzyme Model Reaction-promoting Oscillations and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…occurring between amino acids in a real protein. In a previous publication, we showed that several physical descriptors can be used to predict the average crystallographic temperature factor of a given amino acid residue in the body of cytidine deaminase. This work quantified and modeled the long appreciated fact that amino acid residues enjoy different degrees of conformational freedom in different regions of the enzyme molecule .…”
Section: Enzyme Model Reaction-promoting Oscillations and Methodsmentioning
confidence: 99%
“…These dynamic catalytic strategies augment other recently proposed catalytic mechanisms such as near attack conformers, , whose ground-state substrate molecular geometries resemble that of the transition state for easy and rapid progress over the reaction barrier. Furthermore, speculations that enzyme molecules are evolutionarily architectured so that “stray” or nonproductive fluctuations are minimized are attractive. , Though the above examples mainly address connections between conformational motions and catalysis, the possibility that conformational fluctuations exhibit correlated behavior is under active investigation in other areas of protein science as well. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bagassarian and coworkers122, 123 analyzed the average magnitude of fluctuations in cytidine deaminase complexed with a substrate analog, a transition‐state analog, and the product, and they interpreted the results as if these structures correspond to three successive configurations along the reaction path for the actual substrate. They found the smallest fluctuations at the transition state, a very reasonable result if we believe that the enzyme is evolutionarily adapted to funnel the reactive flux through a configuration with tight binding and maximum transition state stabilization;124 they discussed it as the reaction coordinate “organizing” enzymatic fluctuations.…”
Section: Tunneling In Enzymatic Reactionsmentioning
confidence: 99%
“…In the case of cytidine deaminase, the crystallographic temperature factors for the active site of the cytidine deaminase-substrate complex displayed lower values than those for the cytidine deaminase-TSA complex. 38 This observation suggests that a conformational transition occurs from the flexible conformation in the substrate-bound state to the rigid conformation in the TSA-bound state. In addition, in the case of dihydrofolate reductase, changes in the protein flexibility during the catalytic pathway have been revealed by extensive NMR relaxation analyses, although the difference between the substrate-bound state and the TSA-bound state remain obscure.…”
Section: Comparison With Natural Enzymesmentioning
confidence: 99%